Biliary Adenofibroma of Liver: Morphology, Tumor Genetics, and Outcomes in 6 Cases. (April 2017) - Arnason, Thomas; Borger, Darrell R.; Corless, Christopher; Hagen, Catherine; Iafrate, A. John; Makhlouf, Hala; Misdraji, Joseph; Sapp, Heidi; Tsui, Wilson M.; Wanless, Ian R.; Zuluaga Toro, Tania; Lauwers, Gregory Y.
Abstract : Biliary adenofibroma is a rare primary hepatic neoplasm, recognized in the World Health Organization classification, although only 14 cases have been reported to date. This series includes extended follow-up from 2 of the early case reports and 4 novel cases. Clinical history and histology were reviewed in all 6 cases. Tumor DNA was analyzed for point mutations by multiplex polymerase chain reaction and copy number alterations by array comparative genomic hybridization. The patients included 4 females and 2 males presenting between 46 and 83 years of age, with tumors ranging from 7 to 16 cm in diameter. The tumors had similar morphology, with tubules and cysts lined mainly by bland to mildly atypical cuboidal epithelium embedded in fibrous stroma. Multiplex polymerase chain reaction did not identify mutations in 4 tumors tested. Three tumors tested by array comparative genomic hybridization showed chromosomal copy number alterations, including 1 with amplifications of CCND1 and ERBB2 . Three patients underwent resection with no recurrence at 21, 20, and 3 years of follow-up. One patient is alive after 14 months with no resection. Two patients with margin-positive resections had local recurrence at 1 and 6 years after surgery. No patient had distant metastasis. The distinct morphology and multiple clonal cytogenetic alterations in biliary adenofibromas indicate that the lesions are neoplastic. Amplifications of CCND1 and ERBB2 are not typical of benign neoplasms, and suggest that these tumors may have the ability to behave aggressively. However, the clinical outcomes in these patients suggest the neoplasms are only slowly progressive.